(untitled) (Materiali di Estetica. Terza serie, 2020)
The western civilization with Europe that it has built, is close to the end? Born in Greece with philosophy, when humans responsably wanted to loose a fantastic-mitological vision of reality and chose their lifestyle as something rational, Europe, nowadays, reminding its origins and conscious of its historical realizations, is still able to continue and have progress? According to which conditions?